2020
DOI: 10.1186/s12906-020-03064-6
|View full text |Cite
|
Sign up to set email alerts
|

A botanical from the antiproliferative Cameroonian spice, Imperata cylindrica is safe at lower doses, as demonstrated by oral acute and sub-chronic toxicity screenings

Abstract: Background The cytotoxicity of the root’s methanol extract of Imperata cylindrica (ICR). was previously reported in a panel of human cancer cell lines, including multi-drug resistant phenotypes. The aim of this study was to assess the acute and sub-chronic oral toxicity of methanol root extract of Imperata cylindrica. Methods The acute toxicity was carried out according to the experimental protocol of OECD. The plant extract was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…These findings were in agreement with a recent study that was performed to assess the in vivo toxicological effect of the IC crude extract [30]. This study revealed the safety of crude methanol extract of IC at low doses on animal models, while prolonged use was suggested to be discouraged at high doses.…”
Section: Cell Proliferation Assaysupporting
confidence: 92%
“…These findings were in agreement with a recent study that was performed to assess the in vivo toxicological effect of the IC crude extract [30]. This study revealed the safety of crude methanol extract of IC at low doses on animal models, while prolonged use was suggested to be discouraged at high doses.…”
Section: Cell Proliferation Assaysupporting
confidence: 92%
“…cylindrica root extract which showed that the latter is safe for long-term administration at 500 mg. Kg -1 body weight (bw) (Nayim et al, 2020). Tumor volumes were measured with a digital calliper and calculated using the formula: 1/2 (Length × Width 2 ), where width represents the shortest dimension of the tumor.…”
Section: Caski Xenograft Modelmentioning
confidence: 99%
“…Results displayed by Figure 1 and Table 1 show higher cytotoxicity of IC-MeOH toward nontumor cells than cancer cells that could represent adverse effects. Nonetheless, our previous investigations on IC-MeOH regarding its toxicity in vivo revealed nontoxic effects for acute and repeated administration [ 40 ]. To the best of our knowledge, the present study is highlighting for the first time the antiproliferative mode of action of IC-MeOH toward human cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%